2017
DOI: 10.1186/s13014-017-0895-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of the effects of different radiation qualities on normal human breast cells

Abstract: BackgroundAs there is a growing number of long-term cancer survivors, the incidence of carcinogenesis as a late effect of radiotherapy is getting more and more into the focus. The risk for the development of secondary malignant neoplasms might be significantly increased due to exposure of healthy tissue outside of the target field to secondary neutrons, in particular in proton therapy. Thus far, the radiobiological effects of these neutrons and a comparison with photons on normal breast cells have not been suf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…A similar approach was recently taken by the ANDANTE project [81], a multidisciplinary research collaboration who investigated the risk of neutron carcinogenesis through radiobiological experiments [82], numerical studies [63], and epidemiological models [83]. Building on previous work done by Satoh et al [12] on the depth and energy dependence of secondary charged-particle dose contributions, Baiocco et al [63] studied the depth dependence of single event microdosimetric distributions for external, mono-energetic neutron sources.…”
Section: Microdosimetry In Radiobiologymentioning
confidence: 99%
“…A similar approach was recently taken by the ANDANTE project [81], a multidisciplinary research collaboration who investigated the risk of neutron carcinogenesis through radiobiological experiments [82], numerical studies [63], and epidemiological models [83]. Building on previous work done by Satoh et al [12] on the depth and energy dependence of secondary charged-particle dose contributions, Baiocco et al [63] studied the depth dependence of single event microdosimetric distributions for external, mono-energetic neutron sources.…”
Section: Microdosimetry In Radiobiologymentioning
confidence: 99%
“…We have observed that the 1 MeV mean energy mixed neutron-photon beam proved to be 4 times more effective biologically than the 18 MeV mean energy mixed neutron-photon radiation. The result of the calculated RBE values was well supported by the experiments performed using broad energy spectra, mixed neutron-photon and monoenergetic neutron beams (Juerß et al, 2017). The high reliability of the zebrafish embryo survival assay was revealed during the repeated neutron irradiation experiments, therefore, survival analysis is considered as reliable tool for RBE measurements.…”
Section: Rbe Determination Of Different High Let Neutron Sourcessupporting
confidence: 60%
“…Recent calculations on neutron transport with track structures up to DNA damage induction at different neutron energy levels have provided a better understanding on the physical and biochemical mechanism and have resulted in strong correlation of the RBE to neutron energy (Baiocco et al 2016). The result of the calculated values were well supported by the experiments performed using broad energy spectra, mixed neutron-photon and monoenergetic neutron beams (Juerß et al 2017).…”
Section: Discussionmentioning
confidence: 62%